Studies in Australian Tettigoniidae: New short-winged Agraeciini from Australia (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini) - Rentz, Dcf; Su, You Ning; Ueshima, Norihiro (Zootaxa, 2021)
Descriptions of seven new, short-winged Australian Agraeciine genera are presented with details of distribution, calling songs and karyotypes of several species. Photographs of the habitats of most species are included. A key to the known brachypterous and micropterous Australia agraeciines is presented. A new subtribe Australiagraeciina Rentz, Su, Ueshima is described to include species with small size of adults, macropterous males, apterous females and males with the stridulatory file positioned on a raised swelling. Included in the new subtribe are the following: Australiagraecia Rentz, Su and Ueshima Gen. et sp. nov. with the species A. spina Rentz, Su and Ueshima Gen. et sp. nov. (type species); A. minuta Rentz, Su and Ueshima Gen. et sp. nov.; A. helleri Rentz, Su and Ueshima Gen. et sp. nov.; A. torndirrupa Rentz, Su and Ueshima Gen. et sp. nov.; A. tagera Rentz, Su and Ueshima Gen. et sp. nov.; A. gladiator Rentz, Su and Ueshima Gen. et sp. nov.; A. curvata Rentz, Su and Ueshima Gen. et sp. nov. Ganiagraecia Rentz, Su and Ueshima Gen. nov.; G. karwinia Rentz, Su and Ueshima Gen. et sp. nov. (type species). Gwynnagraecia Rentz, Su and Ueshima Gen. nov.; G. viridis Rentz, Su and Ueshima Gen. et sp. nov. (type species).; G. perplexa Rentz, Su and Ueshima Gen. et sp. nov.; G. marandoo Rentz, Su and Ueshima Gen. et sp. nov. Latitatagraecia Rentz, Su and Ueshima Gen. nov.; L. kalamaya Rentz, Su and Ueshima Gen. et sp. nov. (type species); L. vulgivaga Rentz, Su and Ueshima Gen. et sp. nov. The following are placed in the subtribe Agraeciina Redtenbacher 1891: Cooloolagraecia Rentz, Su and Ueshima Gen. nov.; C. wallum Rentz, Su and Ueshima Gen. et sp. nov. (type species); C. gubbi Rentz, Su and Ueshima Gen. et sp. nov. Kokominiagraecia Rentz, Su and Ueshima Gen. nov.; K. dicra Rentz, Su and Ueshima Gen. et sp. nov. (type species). Timbarragraecia Rentz, Su and Ueshima Gen. nov.; T. samneilli Rentz, Su and Ueshima Gen. et sp. nov. (type species). A key to the Australiagraecia species is included.